Optimizing Gold Recovery of Artisanal Mining: A Lesson Learned from Kenya - Aslam, Izzan Nur; Orcon, Nestor; Klein, Bern; Alam, Pocut Nurul (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2022)
The metallurgical testings to treat the Kenyan artisanal gold mining samples were performed with several processes such as gravity concentration (i.e., Knelson Concentrator and panning), flotation, and cyanidation or leaching. These tests were conducted to find the best processing stages to improve the Kenyan artisanal mining recovery. From the three categories of samples treated, sample A, which was processed through gravity concentration and flotation, produced 95.64% of gold recovery. Meanwhile, sample B could produce 98.74% of gold recovery with the cyanidation test. The results from sample A and sample B confirmed that the combination of the Knelson concentrator and flotation, which the Processing Center should handle, was the perfect combination to reduce the use of cyanide during the leaching process. On the other hand, the study also showed that the tailing sample (sample C) could still be recovered through flotation.With the results obtained, the best scenario was proposed. The government played a critical role in facilitating both the artisanal miners and the Processing Center for both cases, in Kenya or Aceh.